Could we find any signal of the stratosphere-ionosphere coupling in Antarctica? - Carlo Scotto; G. De Franceschi; Edward S. Kazimirovsky; Paolo Grigioni; Marco Pietrella (Annals of Geophysics, 2009)
An investigation searching for a possible coupling between the lower ionosphere and the middle atmosphere in Antarctica is here performed on the basis of stratospheric vertical temperature profiles and ionospheric absorption data observed at the Antarctic Italian Base of Terra Nova Bay (74.69°S, 164.12°E) during local summer time. The result obtained by applying a multi-regression analysis and a Superimposed Epoch Analysis (SEA) shows a statistically significant ionosphere-stratosphere interaction. In particular, by selecting stratospheric temperature maxima occurring at different heights as the referring epoch («zero day») for the SEA approach, the ionospheric absorption is found to show a positive and/or negative trend (several days) around it. The tendency for an increasing/decreasing absorption is obtained for temperature maxima occurring below/above the stratospheric level of about 17-19 km, respectively.